Improving crystal quality of InGaAs/GaAs quantum dots by inductively coupled Ar plasma - Zhang, X. H. (2010)
The crystal quality of InGaAs/GaAs quantum dots (QDs) is substantially improved without redistribution of composition using inductively coupled Ar plasma exposure. After plasma exposure, the QDs exhibit an increase in photoluminescence intensity by a factor of 1.7 while keeping the peak wavelength unshifted, and the band gap blueshift after rapid thermal annealing is suppressed, denoting an improvement in thermal stability. The time-resolved photoluminescence shows an increase in carrier lifetime from 735 to 1140 ps by plasma exposure, indicating the mechanism of grown-in defects reduction in the QD regions.